She-hulk (2004), volume 2 ebook - Slott, Dan (She-Hulk (2004), 2014)
Collects She-Hulk (2004) #7-12. As a superhuman lawyer, She-Hulk has tried some of the strangest cases on Earth... but all of that is about to change! Empowered by the Living Tribunal, Shulkie is heading into deep space to practice Universal Law! Guest-starring Adam Warlock, Gamora, and Pip the Troll! Plus: Out of all of She-Hulk's enemies, no one hates her more than Titania!